Situation Report: Romania, 22 January 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu Pays Working Visit to Oltenita Orthodox Bishop Dismissed Reaction to Ulbricht's Press Conference Foreign Trade Council Established The Reconstruction - A New Political Film Soviet Scientists on European Security Economic News Miscellaneous